Immunity Patterns of Covid-19 Recovered Patients in Gilgit Baltistan, Pakistan - Huda Khan; Maisoor Ahmed Nafees; Saif Ud Din; Mehran Kausar; Raja Imran (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The main purpose of this study was to assess the immunity of recovered patients in COVID-19 patients. The idea was to unveil the nexus between the onset of COVID-19 coupled with the virulence of the disease and the immune responses of the target population in tandem with the intake of local/traditional foods. In the current study antibody presence and complete blood profile of 100 individuals were studied for COVID-19, from the Gilgit area. Immunity against COVID-19 recovered patients was observed during this investigation after more than eight months of their recovery. In this study, 78.2% of people were positive for Immunoglobin G antibody and 23.7% for Immunoglobin M antibody. The most infected age group recorded was 31-40 years. The mean blood glucose level in random was 143.38 mg/dL and 128.18 mg/dL in males and females, respectively. The mean cholesterol level in males was 148.82 mg/dL while the female cholesterol mean was 126.49 mg/dL. White Blood Cells were observed within their prescribed ranges. The mean hemoglobin level was 14.580 g/dL and 12.022 g/dL while mean RBC was 4.7838×106 m/µL and 4.2993×106 m/µL and the mean platelets were 238.45×103/µL and 261.91×103/µL in male and female, respectively. It is observed that the A+ blood group was more susceptible to infection. About 75% of individuals consume highly rich and nutritious food. About 55% of people engaged themselves with exercise. 25% of participants used their normal regular diet during the infection phase on the other hand 75% of individuals treated themselves with a specific and highly nutritious diet for their rapid and healthy recovery. More than 65% of people were re-infected after COVID-19 vaccination but the symptoms were not severe. Due to the strong innate immunity of people from this region, they recovered more rapidly. The dietary habits, high hemoglobin levels coupled with regular exercise might have a positive impact on early recovery of COVID-19-infected patients.